Alumina silicate fiber reinforced coke oven regenerative chamber sealing wall

By using a multi-layered synergistic structure of magnesium-aluminum high-strength insulating bricks, reinforced aluminum silicate fiber blankets, asbestos-free calcium silicate boards, and thermal insulation coatings in the sealing wall of the coke oven regenerator, the problems of insufficient heat insulation, sealing performance, and thermal expansion performance of the sealing wall under high-temperature conditions are solved, achieving more efficient thermal management and a longer service life.

CN121319956APending Publication Date: 2026-01-13LINHUAN COKING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511636955.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-10
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

The existing coke oven regenerator wall has problems with insufficient heat insulation, sealing and thermal expansion performance under high temperature conditions, resulting in increased heat loss, high risk of gas infiltration and cracking, and cannot meet the requirements for long-term service.

Method used

The inner layer is made of magnesium-aluminum high-strength insulating bricks, the middle layer is reinforced aluminum silicate fiber blanket, and the outer layer is made of asbestos-free calcium silicate board and thermal insulation coating. Combined with wire mesh, a multi-layer synergistic structure is formed through staggered masonry, expansion joint filling and high-temperature resistant fixing to enhance thermal insulation and sealing performance.

Benefits of technology

It significantly reduces heat loss, improves sealing and thermal expansion performance, extends the service life of the sealing wall, reduces operation and maintenance costs, and ensures stable thermal efficiency of the coke oven.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an aluminum silicate fiber reinforced coke oven regenerative chamber sealing wall, which belongs to the technical field of coke oven bodies, and specifically comprises the following steps: building magnesium-aluminum high-strength heat-insulating bricks in a staggered joint manner as an inner layer, reserving expansion joints, sequentially paving an aluminum silicate fiber blanket on an outer layer, mounting and fixing an asbestos-free calcium silicate plate, and painting a heat-insulating coating to form a coating, finally, a steel wire mesh is laid and fixed, and the coke oven regenerative chamber sealing wall is obtained. According to the invention, the aluminum silicate fiber blanket is enhanced, and the magnesium-aluminum high-strength heat-insulating brick and the heat-insulating coating are prepared, so that the heat-insulating property, the sealing property and the thermal expansion property of the sealing wall of the regenerative chamber of the coke oven are further optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coke oven body technology, and specifically to a coke oven regenerator sealing wall reinforced with aluminum silicate fiber. Background Technology

[0002] As a core component of the coke oven thermal system, the coke oven regenerator wall must withstand long-term high-temperature fluctuations, airflow impacts, and mechanical loads. At the same time, it must meet excellent thermal insulation, sealing performance, and thermal expansion performance. These three properties directly determine the thermal efficiency, production stability, and service life of the coke oven. However, the coke oven regenerator wall in the currently disclosed technology still has certain defects in material selection, structural design, and construction technology, making it difficult to meet the stringent requirements of long-term high-temperature operation of the coke oven.

[0003] Currently, all layers of wall insulation materials have some defects. Inner insulation materials, such as ordinary clay bricks, are prone to softening and deformation at high temperatures, or have disordered pores leading to insufficient sealing and strength, making them prone to cracking after long-term service, exacerbating heat loss and gas permeation. If the middle layer uses unmodified ordinary aluminum silicate fiber blankets, the large fiber gaps and lack of stable structure cause shrinkage and deformation at high temperatures, weakening the insulation effect and failing to buffer thermal stress differences, leading to wall cracking and delamination. In terms of outer protective insulation, some use calcium silicate boards containing asbestos, which are not environmentally friendly and have poor joint treatment, and the high-temperature sealant is prone to failure, leading to gas permeation. The outer insulation coatings are mostly single-component, with limited insulation performance and lack of structural reinforcement layers. Some do not have protective netting or use ordinary wire mesh, which is prone to rust and cannot disperse local stress, resulting in paint peeling and board cracking.

[0004] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a coke oven regenerator sealing wall reinforced with aluminum silicate fiber, which solves the technical problems of insufficient thermal insulation, sealing performance and thermal expansion performance of the coke oven regenerator sealing wall in the prior art.

[0006] The objective of this invention can be achieved through the following technical solution: a coke oven regenerator sealing wall reinforced with aluminosilicate fiber, wherein the coke oven regenerator sealing wall structure consists of, from the inside out, magnesium-aluminum high-strength heat-insulating bricks, reinforced aluminosilicate fiber blankets, asbestos-free calcium silicate boards, heat-insulating coatings, and wire mesh.

[0007] Furthermore, the magnesium-aluminum high-strength insulating brick is prepared by the following steps:

[0008] A1. Add fused magnesia, p-Al2O3 and α-Al2O3 to a ball mill and ball mill for 6-8 hours. Then add them to the auxiliary additive liquid and stir for 30-60 minutes to obtain a mixed slurry.

[0009] A2. Add the foaming agent and deionized water to a high-speed mixer and stir at 2000 r / min for 5-10 minutes. Then mix with the slurry and continue stirring for 5-10 minutes. Pour into a mold and perform post-processing to obtain magnesium-aluminum high-strength heat-insulating bricks.

[0010] Reaction principle:

[0011] Ball milling refines and uniformly mixes fused magnesia, ρ-Al2O3, and α-Al2O3 particles. PVA adhesive in the auxiliary additive solution plays a binding role, and sodium tripolyphosphate promotes particle dispersion, forming a stable mixed slurry. Sodium dodecyl sulfate generates bubbles through high-speed stirring and is uniformly dispersed in the slurry. The curing and drying process removes moisture, and the PVA adhesive solidifies to maintain the shape of the green body. During high-temperature sintering, MgO and Al2O3 undergo a solid-phase reaction to generate a high-strength magnesium-aluminum spinel phase. At the same time, the sintering and densification between particles enhances the structural strength, while the pores formed by foaming are partially retained at high temperatures, giving the material thermal insulation properties. Finally, a magnesium-aluminum high-strength thermal insulation brick with both high strength and good thermal insulation properties is formed.

[0012] Further, in step A1, the ratio of the amount of fused magnesia, p-Al2O3, α-Al2O3, and auxiliary additive is 7g:5-6g:10-12g:25mL, and the auxiliary additive is obtained by uniformly mixing PVA adhesive, sodium tripolyphosphate, and deionized water at a ratio of 1g:0.2g:100mL; in step A2, the foaming agent is sodium dodecyl sulfate, and the ratio of the foaming agent, deionized water, and mixed slurry is 0.5g. The post-processing operation includes: after being injected into the mold, curing at 20-30℃ and 60%-80% relative humidity for 24 hours, demolding, placing the green body in a drying oven, drying at 60℃ for 12 hours, then raising the temperature to 120℃ for 36 hours, and finally placing the dried green body in a high-temperature sintering furnace, sintering at 1500-1700℃ for 3-5 hours, and then cooling to room temperature to obtain magnesium-aluminum high-strength heat-insulating bricks.

[0013] Furthermore, the reinforced aluminosilicate fiber blanket is prepared by the following steps:

[0014] B1. Add tetraethyl orthosilicate, anhydrous ethanol and deionized water to the reaction vessel, then add ammonia dropwise until the pH of the solution reaches 8-9, stir for 10-12 hours to obtain silica sol;

[0015] B2. Add silica sol, borax, aluminum nitrate and deionized water together into the reaction vessel, and ultrasonically disperse at 20-30℃ for 10-20 min. Then raise the temperature to 45-55℃ and stir for 5-6 h to obtain a mixed solution.

[0016] B3. Immerse the aluminum silicate fiber blanket completely in the mixed solution under vacuum conditions for 20-30 minutes. Repeat the immersion 3-4 times. After post-treatment, the reinforced aluminum silicate fiber blanket is obtained.

[0017] Reaction principle:

[0018] Tetraethyl orthosilicate undergoes hydrolysis under alkaline conditions regulated by ammonia to produce silicic acid, which then condenses to form a silica sol containing nano-SiO2 particles. The silica sol reacts with borate ions dissociated from borax and Al ions dissociated from aluminum nitrate. 3+ The mixture is uniformly mixed under ultrasonic dispersion and stirred at 45-55℃ to undergo composite condensation, forming a composite sol precursor containing Si, B, and Al elements. Then, the aluminosilicate fiber blanket is impregnated under vacuum to allow the composite sol to fully penetrate into the fiber gaps. After drying to remove the solvent, high-temperature treatment promotes further condensation of the precursor to form covalently bonded ceramic phases such as Si-OB and Si-O-Al. These phases fill the fiber gaps to form a reinforced bridging structure, thereby enhancing the overall strength and structural stability of the aluminosilicate fiber blanket.

[0019] Further, in step B1, the amounts of tetraethyl orthosilicate, anhydrous ethanol, and deionized water are 1g:3-5mL:4-6mL, and the mass fraction of ammonia is 25%; in step B2, the ratio of silica sol, borax, aluminum nitrate, and deionized water is 5g:0.2-0.4g:0.8-1.2g:2-3mL; in step B3, the post-treatment operation includes: after impregnation, placing the fiber blanket in a drying oven, drying it at 80℃ for 12 hours, and then keeping it at 900-1000℃ for 2-4 hours to obtain a reinforced aluminum silicate fiber blanket.

[0020] Furthermore, the aluminosilicate fiber-reinforced coke oven regenerator sealing wall is prepared by the following steps:

[0021] S1. Magnesium-aluminum high-strength heat-insulating bricks are used as the inner structure, and staggered joint masonry is adopted. High-temperature adhesive is used to fill the gaps between the bricks. A 2-3mm expansion joint is reserved at the contact surface between the magnesium-aluminum high-strength heat-insulating bricks and the main wall and single wall, and the joint is filled with ceramic fiber rope.

[0022] S2. Lay reinforced aluminum silicate fiber blankets on the outer layer of magnesium-aluminum high-strength heat-insulating bricks, using a layered overlapping method, with an overlap width of 100-110mm between each layer of fiber blankets, and fix the overlap with high-temperature resistant stainless steel clips.

[0023] S3. Install asbestos-free calcium silicate boards on the outer layer of the reinforced aluminum silicate fiber blanket. The boards are arranged horizontally with staggered seams. Use high-temperature resistant expansion bolts with heat insulation pads to fix the calcium silicate boards to the base bricks. The bolt spacing is 400×400mm. Fill the gaps between the boards and the main wall and single walls with fireproof sealant.

[0024] S4. Apply thermal insulation coating evenly to the surface of the asbestos-free calcium silicate board in two layers. The thickness of the first layer should be controlled at 10-20mm. After it is completely dry, apply the second layer. The total thickness should reach 40-50mm to form a thermal insulation coating on the surface of the asbestos-free calcium silicate board.

[0025] S5. Lay wire mesh on the surface of the thermal insulation coating. The overlap width between the wire mesh sheets is 50-60mm. The overlap is tied firmly with binding wire. Then, use high-temperature resistant expansion bolts to fix the wire mesh to the wall. The bolt spacing is 300×300mm to obtain the sealing wall of the coke oven regenerator.

[0026] Further, in step S4, the preparation method of the high-temperature resistant thermal insulation coating is as follows: sodium hexametaphosphate and deionized water are added to a mixer and stirred for 10-15 minutes. Then, silica powder and silicon nitride powder are added and stirred for another 20-30 minutes. The mixture is then passed through a 300-mesh sieve, hollow ceramic microspheres are added, and the mixture is stirred for 10-15 minutes. Finally, the mixture is transferred to a sand mill and ground for 30-40 minutes to obtain the high-temperature resistant thermal insulation coating.

[0027] Furthermore, the ratio of sodium hexametaphosphate, deionized water, silica powder, silicon nitride powder, and hollow ceramic microspheres is 0.4g:22-25mL:20g:1.8g:38-45g.

[0028] The present invention has the following beneficial effects:

[0029] 1. The magnesium-aluminum high-strength insulating brick of the present invention serves as the inner base layer. It is sintered at high temperature to form a dense structure with closed pores, which can block the heat conduction of the inner layer. The reinforcing aluminum silicate fiber blanket is laid in layers and overlapped and fixed, and is tightly attached to the outer layer of the insulating brick. It can fill the gaps in the brickwork and further weaken the heat transfer through the low thermal conductivity of the fiber itself. The outer layer of heat insulation coating is uniformly covered on the surface of the asbestos-free calcium silicate board. The hollow ceramic microspheres contained therein can build an additional heat insulation barrier and fill the micropores and gaps of the board. In addition, the wall preparation process includes the reserved expansion joints and filling with ceramic fiber ropes, staggered arrangement of the board, etc., so that the materials of each layer complement each other in terms of heat insulation function, effectively reduce heat loss, reduce the overall thermal conductivity, and improve the heat insulation performance of the coke oven regenerator wall.

[0030] 2. The magnesium-aluminum high-strength insulating bricks of this invention use high-temperature adhesive to fill the brick joints, combined with a staggered masonry method, to reduce the interconnected pores between the bricks. The reinforced aluminosilicate fiber blankets, after vacuum impregnation, have their fiber gaps filled with a ceramic phase, reducing their porosity. Furthermore, the overlaps are fixed with high-temperature resistant stainless steel clips, preventing gaps between the fiber blanket layers. The asbestos-free calcium silicate boards are arranged horizontally with staggered joints. The gaps between the boards and the main wall and individual walls are filled with fire-retardant sealant. The bolt fixing method with heat-insulating pads further blocks gas permeation channels at the bolt holes. The outer insulating coating forms a continuous sealing layer, covering the micropores and joints on the board surface. Each layer of material gradually seals potential gas channels from the inner to the outer layer, collaboratively constructing a dense sealing structure, reducing interconnected pores, lowering apparent porosity, and improving the sealing performance of the coke oven regenerator wall.

[0031] 3. In this invention, the inner layer of high-strength magnesium-aluminum insulating bricks is sintered at high temperature to form a stable magnesium-aluminum spinel phase, which possesses controllable expansion characteristics. Furthermore, the staggered joint construction method further disperses local expansion stress, laying a rigid foundation for controlling the overall expansion coefficient of the sealing wall. This prevents the overall coefficient from becoming uncontrollable due to abnormal expansion of the inner layer material. The middle layer of reinforced aluminosilicate fiber blankets, after being treated with ceramic phase reinforcement, retains the flexible expansion buffering capacity of the fiber material while improving expansion stability through the ceramic bridging structure between fibers. This precisely harmonizes the expansion differences between the inner and outer insulating bricks, dissolving the thermal stress caused by different expansion rates between layers and preventing delamination or cracking of the sealing wall. The outer layer... The thermal insulation coating, relying on its hollow ceramic microspheres and other components, forms a highly efficient thermal insulation barrier while adapting to the overall expansion trend through its own structural characteristics. The continuous coating form can fill the gaps between the outer plates, avoiding coefficient fluctuations caused by uneven local expansion. The three elements form a synergistic system of "rigid foundation controlling expansion - flexible intermediate adjusting differences - outer layer adapting to compensate for defects". This allows the overall thermal expansion coefficient of the sealing wall to accurately match the expansion characteristics of the coke oven's main wall and individual walls, effectively resisting the thermal stress caused by temperature fluctuations in the coke oven's "heat storage-heat release" cycle. This significantly reduces the risk of sealing wall cracking and gas leakage, ensures stable coke oven thermal efficiency, extends the service life of the sealing wall, and reduces operation and maintenance costs. Detailed Implementation

[0032] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] In this invention, the aluminum silicate fiber blanket is selected from Baotou Runqing Thermal Insulation and Waterproof Materials Co., Ltd., and has a thickness of 50mm;

[0034] In this invention, the asbestos-free calcium silicate board is selected from Jiangxi Annei Construction and Installation Engineering Co., Ltd., and has a fire resistance rating of A1.

[0035] In this invention, the wire mesh is selected from Hebei Anbai Wire Mesh Products Co., Ltd., with an aperture of 0.6cm and product number AB-3289;

[0036] In this invention, the high-temperature adhesive is selected from Langfang Lesen Environmental Protection Technology Co., Ltd., and the brand name is Lesen.

[0037] In this invention, the ceramic fiber rope is selected from Weifang Xinwanjia Sealing Materials Co., Ltd., and has a thickness of 0.15mm;

[0038] In this invention, the ceramic anchor is selected from Sanmenxia Tianbao Special Refractory Fiber Co., Ltd., and is nail-shaped;

[0039] In this invention, the high-temperature resistant expansion bolt is selected from Wuxi Baike Hardware Products Co., Ltd., with a length of 50mm and model number Baike-240814-wu-01;

[0040] In this invention, the hollow ceramic microspheres are selected from Guangdong Huolun Building Materials Technology Development Co., Ltd., with a thermal conductivity of 0.034 W / (m·K), and the brand is Naiboshi.

[0041] In this application, the silica powder is selected from Lianyungang Weisheng Silicon Materials Co., Ltd., and the particle size is 5μm.

[0042] In this application, the silicon nitride powder is selected from Shanghai Yingfeng Ruihuang Metal Materials Co., Ltd., with a particle size of 20,000 mesh and a grade of 005588.

[0043] Example 1

[0044] This embodiment provides a coke oven regenerator wall reinforced with aluminosilicate fiber, comprising the following steps:

[0045] S1. Preparation of magnesium-aluminum high-strength heat-insulating bricks

[0046] Weigh out 10g of PVA glue, 2g of sodium tripolyphosphate and 1L of deionized water and mix them evenly to obtain the auxiliary additive solution;

[0047] Weigh out 70g of fused magnesia, 50g of ρ-Al2O3 and 100g of α-Al2O3 and add them to a ball mill and ball mill for 6 hours. Then add them to 250mL of auxiliary additive liquid and stir for 30 minutes to obtain a mixed slurry.

[0048] Weigh out 5g of sodium dodecyl sulfate and 200mL of deionized water and add them to a high-speed mixer. Stir at 2000r / min for 5min, then mix with 1000g of mixed slurry and continue stirring for 5min. Pour the mixture into a mold and cure at 20℃ and 60% relative humidity for 24h. Demold the mold and place the green body in a drying oven. First, dry at 60℃ for 12h, then raise the temperature to 120℃ and dry for 36h. Finally, place the dried green body in a high-temperature sintering furnace and sinter at 1500℃ for 3h. Cool to room temperature to obtain magnesium-aluminum high-strength heat-insulating bricks.

[0049] S2, Preparation of reinforced aluminosilicate fiber blankets

[0050] Weigh out 10g of tetraethyl orthosilicate, 30mL of anhydrous ethanol and 40mL of deionized water and add them to the reaction vessel. Then add 25wt% ammonia dropwise until the pH of the solution reaches 8. Stir for 10h to obtain silica sol.

[0051] Weigh out 50g of silica sol, 2g of borax, 8g of aluminum nitrate and 20mL of deionized water and add them to the reaction vessel. Disperse the mixture by ultrasonication at 20℃ for 10min, then heat to 45℃ and stir for 5h to obtain a mixed solution.

[0052] The aluminum silicate fiber blanket was completely immersed in the mixed solution under vacuum conditions for 20 minutes. The immersion was repeated 3 times. After post-treatment, the reinforced aluminum silicate fiber blanket was obtained.

[0053] S3. Preparation of high-temperature resistant thermal insulation coating

[0054] Weigh out 4g of sodium hexametaphosphate and 220mL of deionized water and add them to a mixer and stir for 10 minutes. Then add 200g of silica powder and 18g of silicon nitride powder and continue stirring for 20 minutes. Pass the mixture through a 300-mesh sieve and add 280g of hollow ceramic microspheres. Stir for 10 minutes and then transfer the mixture to a sand mill and grind for 30 minutes to obtain a high-temperature resistant thermal insulation coating.

[0055] S4. Preparation of the sealing wall for the coke oven regenerator

[0056] The inner structure is made of magnesium-aluminum high-strength heat-insulating bricks, and a staggered joint masonry method is adopted. The bricks are filled with high-temperature adhesive. A 2mm expansion joint is reserved at the contact surface between the magnesium-aluminum high-strength heat-insulating bricks and the main wall and single wall, and the joint is filled with ceramic fiber rope.

[0057] A reinforced aluminum silicate fiber blanket is laid on the outer layer of the magnesium-aluminum high-strength heat-insulating brick. The layered laying method is adopted, with an overlap width of 100mm between each layer of fiber blanket. The overlap is fixed with high-temperature resistant stainless steel clips.

[0058] Asbestos-free calcium silicate boards are installed on the outer layer of the reinforced aluminum silicate fiber blanket. The boards are arranged horizontally with staggered seams. The calcium silicate boards are fixed to the base bricks using high-temperature resistant expansion bolts with heat insulation pads. The bolt spacing is 400×400mm. The gaps between the boards and the main wall and single walls are filled with fireproof sealant.

[0059] Apply thermal insulation coating evenly to the surface of the asbestos-free calcium silicate board in two layers. The first layer is 10mm thick. After it is completely dry, apply the second layer. The total thickness is 40mm, forming a thermal insulation coating on the surface of the asbestos-free calcium silicate board.

[0060] A wire mesh is laid on the surface of the thermal insulation coating, with an overlap width of 50mm between the wire mesh panels. The overlaps are secured with binding wire. The wire mesh is then fixed to the wall using high-temperature resistant expansion bolts with a bolt spacing of 300×300mm, thus obtaining the sealing wall of the coke oven regenerator.

[0061] Example 2

[0062] This embodiment provides a coke oven regenerator wall reinforced with aluminosilicate fiber, comprising the following steps:

[0063] S1. Preparation of magnesium-aluminum high-strength heat-insulating bricks

[0064] Weigh out 10g of PVA glue, 2g of sodium tripolyphosphate and 1L of deionized water and mix them evenly to obtain the auxiliary additive solution;

[0065] Weigh out 70g of fused magnesia, 55g of ρ-Al2O3 and 110g of α-Al2O3 and add them to a ball mill and ball mill for 7 hours. Then add them to 250mL of auxiliary additive liquid and stir for 45 minutes to obtain a mixed slurry.

[0066] Weigh out 5g of sodium dodecyl sulfate and 200mL of deionized water and add them to a high-speed mixer. Stir at 2000r / min for 8 minutes, then mix with 1000g of mixed slurry and continue stirring for 8 minutes. Pour the mixture into a mold and cure it at 25℃ and 70% relative humidity for 24 hours. Demold the mold and place the green body in a drying oven. First, dry it at 60℃ for 12 hours, then raise the temperature to 120℃ and dry it for 36 hours. Finally, place the dried green body in a high-temperature sintering furnace and sinter it at 1600℃ for 4 hours. After cooling to room temperature, you will get magnesium-aluminum high-strength heat-insulating bricks.

[0067] S2, Preparation of reinforced aluminosilicate fiber blankets

[0068] Weigh out 10g of tetraethyl orthosilicate, 40mL of anhydrous ethanol and 50mL of deionized water and add them to the reaction vessel. Then add 25wt% ammonia dropwise until the pH of the solution reaches 8.5. Stir for 11 hours to obtain silica sol.

[0069] Weigh out 50g of silica sol, 3g of borax, 10g of aluminum nitrate and 25mL of deionized water and add them to the reaction vessel. Disperse the mixture by ultrasonication at 25℃ for 15min, then heat to 50℃ and stir for 5.5h to obtain a mixed solution.

[0070] The aluminum silicate fiber blanket was completely immersed in the mixed solution under vacuum conditions for 25 minutes. The immersion was repeated 3 times. After post-treatment, the reinforced aluminum silicate fiber blanket was obtained.

[0071] S3. Preparation of high-temperature resistant thermal insulation coating

[0072] Weigh out 4g of sodium hexametaphosphate and 230mL of deionized water and add them to a mixer and stir for 10 minutes. Then add 200g of silica powder and 18g of silicon nitride powder and continue stirring for 25 minutes. Pass the mixture through a 300-mesh sieve and add 350g of hollow ceramic microspheres. Stir for 10 minutes and then transfer the mixture to a sand mill and grind for 35 minutes to obtain a high-temperature resistant thermal insulation coating.

[0073] S4. Preparation of the sealing wall for the coke oven regenerator

[0074] The inner structure is made of magnesium-aluminum high-strength heat-insulating bricks, and a staggered joint masonry method is adopted. The bricks are filled with high-temperature adhesive. A 2mm expansion joint is reserved at the contact surface between the magnesium-aluminum high-strength heat-insulating bricks and the main wall and single wall, and the joint is filled with ceramic fiber rope.

[0075] A reinforced aluminum silicate fiber blanket is laid on the outer layer of the magnesium-aluminum high-strength heat-insulating brick. The layered laying method is adopted, with an overlap width of 105mm between each layer of fiber blanket. The overlap is fixed with high-temperature resistant stainless steel clips.

[0076] Asbestos-free calcium silicate boards are installed on the outer layer of the reinforced aluminum silicate fiber blanket. The boards are arranged horizontally with staggered seams. The calcium silicate boards are fixed to the base bricks using high-temperature resistant expansion bolts with heat insulation pads. The bolt spacing is 400×400mm. The gaps between the boards and the main wall and single walls are filled with fireproof sealant.

[0077] Apply thermal insulation coating evenly to the surface of the asbestos-free calcium silicate board in two layers. The first layer is 15mm thick. After it is completely dry, apply the second layer. The total thickness is 45mm, forming a thermal insulation coating on the surface of the asbestos-free calcium silicate board.

[0078] A wire mesh is laid on the surface of the thermal insulation coating, with an overlap width of 55mm between the wire mesh panels. The overlaps are secured with binding wire. The wire mesh is then fixed to the wall using high-temperature resistant expansion bolts with a bolt spacing of 300×300mm, thus obtaining the sealing wall of the coke oven regenerator.

[0079] Example 3

[0080] This embodiment provides a coke oven regenerator wall reinforced with aluminosilicate fiber, comprising the following steps:

[0081] S1. Preparation of magnesium-aluminum high-strength heat-insulating bricks

[0082] Weigh out 10g of PVA glue, 2g of sodium tripolyphosphate and 1L of deionized water and mix them evenly to obtain the auxiliary additive solution;

[0083] Weigh out 70g of fused magnesia, 60g of ρ-Al2O3 and 120g of α-Al2O3 and add them to a ball mill and ball mill for 8 hours. Then add them to 250mL of auxiliary additive liquid and stir for 60 minutes to obtain a mixed slurry.

[0084] Weigh out 5g of sodium dodecyl sulfate and 200mL of deionized water and add them to a high-speed mixer. Stir at 2000r / min for 10min, then mix with 1000g of mixed slurry and continue stirring for 10min. Pour the mixture into a mold and cure at 30℃ and 80% relative humidity for 24h. Demold the mold and place the green body in a drying oven. First, dry at 60℃ for 12h, then raise the temperature to 120℃ and dry for 36h. Finally, place the dried green body in a high-temperature sintering furnace and sinter at 1700℃ for 5h. Cool to room temperature to obtain magnesium-aluminum high-strength heat-insulating bricks.

[0085] S2, Preparation of reinforced aluminosilicate fiber blankets

[0086] Weigh out 10g of tetraethyl orthosilicate, 50mL of anhydrous ethanol and 60mL of deionized water and add them to the reaction vessel. Then add 25wt% ammonia dropwise until the pH of the solution reaches 9. Stir for 12h to obtain silica sol.

[0087] Weigh out 50g of silica sol, 4g of borax, 12g of aluminum nitrate and 30mL of deionized water and add them to the reaction vessel. Disperse the mixture by ultrasonication at 30℃ for 20min, then heat to 55℃ and stir for 6h to obtain a mixed solution.

[0088] The aluminum silicate fiber blanket was completely immersed in the mixed solution under vacuum conditions for 30 minutes. The immersion was repeated 4 times. After post-treatment, the reinforced aluminum silicate fiber blanket was obtained.

[0089] S3. Preparation of high-temperature resistant thermal insulation coating

[0090] Weigh out 4g of sodium hexametaphosphate and 250mL of deionized water and add them to a mixer and stir for 15 minutes. Then add 200g of silica powder and 18g of silicon nitride powder and continue stirring for 30 minutes. Pass the mixture through a 300-mesh sieve and add 450g of hollow ceramic microspheres. Stir for 15 minutes and then transfer the mixture to a sand mill and grind for 40 minutes to obtain a high-temperature resistant thermal insulation coating.

[0091] S4. Preparation of the sealing wall for the coke oven regenerator

[0092] The inner structure is made of magnesium-aluminum high-strength heat-insulating bricks, and a staggered joint masonry method is adopted. The bricks are filled with high-temperature adhesive. A 3mm expansion joint is reserved at the contact surface between the magnesium-aluminum high-strength heat-insulating bricks and the main wall and single wall, and the joint is filled with ceramic fiber rope.

[0093] A reinforced aluminum silicate fiber blanket is laid on the outer layer of the magnesium-aluminum high-strength heat-insulating brick. The layered laying method is adopted, with an overlap width of 110mm between each layer of fiber blanket. The overlap is fixed with high-temperature resistant stainless steel clips.

[0094] Asbestos-free calcium silicate boards are installed on the outer layer of the reinforced aluminum silicate fiber blanket. The boards are arranged horizontally with staggered seams. The calcium silicate boards are fixed to the base bricks using high-temperature resistant expansion bolts with heat insulation pads. The bolt spacing is 400×400mm. The gaps between the boards and the main wall and single walls are filled with fireproof sealant.

[0095] Apply thermal insulation coating evenly to the surface of the asbestos-free calcium silicate board in two layers. The first layer is 20mm thick. After it is completely dry, apply the second layer. The total thickness is 50mm, forming a thermal insulation coating on the surface of the asbestos-free calcium silicate board.

[0096] A wire mesh is laid on the surface of the thermal insulation coating, with an overlap width of 60mm between the wire mesh panels. The overlaps are secured with binding wire. High-temperature resistant expansion bolts are then used to fix the wire mesh to the wall, with a bolt spacing of 300×300mm, thus obtaining the sealing wall of the coke oven regenerator.

[0097] Comparative Example 1

[0098] The difference between this comparative example and Example 3 is that step S1 is omitted, and the magnesium-aluminum high-strength insulating brick in step S4 is replaced with clay insulating brick.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 3 is that step S2 is omitted, and the aluminum silicate fiber blanket in step S4 is replaced with the aluminum silicate fiber blanket in step S2.

[0101] Comparative Example 3

[0102] The difference between this comparative example and Example 3 is that step S3 is omitted, and the thermal insulation coating is not applied to the surface of the asbestos-free calcium silicate board.

[0103] Comparative Example 4

[0104] The difference between this comparative example and Example 3 is that no wire mesh is added to the surface of the sealing wall.

[0105] Performance testing:

[0106] The thermal conductivity of the prepared magnesium-aluminum high-strength insulating brick was determined according to the standard YB / T 4130-2005 "Test Method for Thermal Conductivity of Refractory Materials (Water Flow Plate Method)".

[0107] The high-temperature flexural strength of the prepared magnesium-aluminum high-strength insulating bricks was determined according to the standard GB / T 3002-2017 "Test Method for High-Temperature Flexural Strength of Refractory Materials".

[0108] The apparent porosity of the prepared magnesium-aluminum high-strength insulating bricks was determined according to standard GB / T 2997-2015 "Test Methods for Bulk Density, Apparent Porosity and True Porosity of Dense Shaped Refractory Products". The specific test results are shown in Tables 1 and 2 below:

[0109] Table 1 - Basic Performance Test Data of Magnesium-Aluminum High-Strength Insulating Bricks

[0110]

[0111] Table 2 - Basic Performance Test Data of Reinforced Aluminosilicate Fiber Blanket

[0112]

[0113] The thermal conductivity of the coke oven regenerator sealing walls prepared in Examples 1-3 and Comparative Examples 1-4 was determined in accordance with the standard YB / T 4130-2005 "Test Method for Thermal Conductivity of Refractory Materials (Water Flow Plate Method)".

[0114] The coefficients of thermal expansion of the coke oven regenerator sealing walls prepared in Examples 1-3 and Comparative Examples 1-4 were determined according to standard GB / T 3810.8-2016 "Test Methods for Ceramic Tiles - Part 8: Determination of Linear Thermal Expansion". The specific test results are shown in Table 3 below:

[0115] Table 3 - Basic Performance Test Data of Coke Oven Regenerator Sealing Wall

[0116]

[0117] Data Analysis:

[0118] Table 3 shows that Examples 1-3 constructed a multi-layered synergistic system consisting of magnesium-aluminum high-strength insulating bricks, reinforced aluminum silicate fiber blankets, asbestos-free calcium silicate boards, and thermal insulation coatings. Through staggered masonry and filling expansion joints with ceramic fiber ropes to eliminate gaps, heat transfer was blocked, pores were sealed, and stress was evenly distributed, resulting in a thermal conductivity of 0.055-0.059 W / (m·K) and a coefficient of thermal expansion of 12.2-12.7 (×10⁻⁶). -6 / ℃);

[0119] In Table 1, in Examples 1-3, the thermal conductivity of the magnesium-aluminum high-strength insulating bricks gradually decreased, the apparent porosity slightly decreased, and the high-temperature flexural strength gradually increased. This is because in Examples 1-3, the ball milling time was extended and the sintering temperature was increased, which made the fused magnesia and Al2O3 particles finer and more uniform, the magnesium-aluminum spinel phase more fully formed, and the closed pores more regular. This not only reduced the heat transfer channels but also improved the structural density and grain boundary bonding. The auxiliary additives ensured the early strength of the green body, and finally achieved synergistic optimization of thermal insulation and strength performance.

[0120] In Table 2, in Examples 1-3, the thermal conductivity of the reinforced aluminosilicate fiber blanket gradually decreased, the apparent porosity slightly decreased, and the high-temperature flexural strength gradually increased. This is because in Examples 1-3, the ultrasonic dispersion time was extended, the number of vacuum impregnations was increased, and the sintering temperature was raised, which allowed the composite sol to penetrate into the fiber gaps more evenly, resulting in a more perfect Si-OB / Si-O-Al ceramic bridging structure. This not only reduced the heat transfer gaps but also enhanced the bonding force between fibers, while retaining the porous characteristics of the fibers, thus improving thermal insulation and structural stability.

[0121] In Table 3, in Examples 1-3, the thermal conductivity of the sealing wall gradually decreased and the coefficient of thermal expansion slightly decreased. This was due to the synergistic optimization of the performance of the inner layer of magnesium-aluminum bricks, the middle layer of reinforcing fiber blanket, and the outer layer of thermal insulation coating, as well as the reduction of heat loss and expansion stress by processes such as staggered masonry and expansion joint filling. In Comparative Examples 1-4, the performance deteriorated significantly. This was because Comparative Example 1 used clay bricks lacking a stable spinel phase, Comparative Example 2 used ordinary fiber blankets without ceramic reinforcement, Comparative Example 3 eliminated the thermal insulation coating and lacked a thermal insulation barrier, and Comparative Example 4 eliminated the wire mesh and lacked stress dispersion. All of these factors destroyed the synergistic effect of the multi-layer materials, resulting in poor thermal insulation and thermal expansion performance.

[0122] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A coke oven regenerator sealing wall reinforced with aluminosilicate fiber, characterized in that, The sealing wall structure of the coke oven regenerator consists of, from the inside out, magnesium-aluminum high-strength insulating bricks, reinforced aluminum silicate fiber blankets, asbestos-free calcium silicate boards, thermal insulation coatings, and wire mesh.

2. The coke oven regenerator sealing wall reinforced with aluminosilicate fiber according to claim 1, characterized in that, The magnesium-aluminum high-strength heat-insulating brick is prepared by the following steps: A1. Add fused magnesia, p-Al2O3 and α-Al2O3 to a ball mill and ball mill for 6-8 hours. Then add them to the auxiliary additive liquid and stir for 30-60 minutes to obtain a mixed slurry. A2. Add the foaming agent and deionized water to a high-speed mixer and stir at 2000 r / min for 5-10 minutes. Then mix with the slurry and continue stirring for 5-10 minutes. Pour into a mold and perform post-processing to obtain magnesium-aluminum high-strength heat-insulating bricks.

3. The coke oven regenerator sealing wall reinforced with aluminosilicate fiber according to claim 2, characterized in that, In step A1, the ratio of fused magnesia, p-Al2O3, α-Al2O3, and auxiliary additive solution is 7g:5-6g:10-12g:25mL. The auxiliary additive solution is obtained by uniformly mixing PVA adhesive, sodium tripolyphosphate, and deionized water at a ratio of 1g:0.2g:100mL. In step A2, the foaming agent is sodium dodecyl sulfate, and the ratio of the foaming agent, deionized water, and mixed slurry is 0.5g:20g. mL:100g, the post-processing operation includes: after being injected into the mold, curing for 24 hours at 20-30℃ and 60%-80% relative humidity, demolding, placing the green body in a drying oven, drying at 60℃ for 12 hours, then raising the temperature to 120℃ for 36 hours, and finally placing the dried green body in a high-temperature sintering furnace, sintering at 1500-1700℃ for 3-5 hours, and cooling to room temperature to obtain magnesium-aluminum high-strength heat-insulating brick.

4. The coke oven regenerator sealing wall reinforced with aluminosilicate fiber according to claim 1, characterized in that, The reinforced aluminosilicate fiber blanket is prepared by the following steps: B1. Add tetraethyl orthosilicate, anhydrous ethanol and deionized water to the reaction vessel, then add ammonia dropwise until the pH of the solution reaches 8-9, stir for 10-12 hours to obtain silica sol; B2. Add silica sol, borax, aluminum nitrate and deionized water together into the reaction vessel, and ultrasonically disperse at 20-30℃ for 10-20 min. Then raise the temperature to 45-55℃ and stir for 5-6 h to obtain a mixed solution. B3. Immerse the aluminum silicate fiber blanket completely in the mixed solution under vacuum conditions for 20-30 minutes. Repeat the immersion 3-4 times. After post-treatment, the reinforced aluminum silicate fiber blanket is obtained.

5. The coke oven regenerator sealing wall reinforced with aluminosilicate fiber according to claim 4, characterized in that, In step B1, the amounts of tetraethyl orthosilicate, anhydrous ethanol, and deionized water are 1g:3-5mL:4-6mL, and the mass fraction of ammonia is 25%; in step B2, the ratio of silica sol, borax, aluminum nitrate, and deionized water is 5g:0.2-0.4g:0.8-1.2g:2-3mL. In step B3, the post-processing operation includes: after impregnation, the fiber blanket is placed in a drying oven and dried at 80°C for 12 hours, and then kept at 900-1000°C for 2-4 hours to obtain a reinforced aluminum silicate fiber blanket.

6. The coke oven regenerator sealing wall reinforced with aluminosilicate fiber according to claim 1, characterized in that, The aluminosilicate fiber-reinforced coke oven regenerator sealing wall is prepared by the following steps: S1. Magnesium-aluminum high-strength heat-insulating bricks are used as the inner structure, and staggered joint masonry is adopted. High-temperature adhesive is used to fill the gaps between the bricks. A 2-3mm expansion joint is reserved at the contact surface between the magnesium-aluminum high-strength heat-insulating bricks and the main wall and single wall, and the joint is filled with ceramic fiber rope. S2. Lay reinforced aluminum silicate fiber blankets on the outer layer of magnesium-aluminum high-strength heat-insulating bricks, using a layered overlapping method, with an overlap width of 100-110mm between each layer of fiber blankets, and fix the overlap with high-temperature resistant stainless steel clips. S3. Install asbestos-free calcium silicate boards on the outer layer of the reinforced aluminum silicate fiber blanket. The boards are arranged horizontally with staggered seams. Use high-temperature resistant expansion bolts with heat insulation pads to fix the calcium silicate boards to the base bricks. The bolt spacing is 400×400mm. Fill the gaps between the boards and the main wall and single walls with fireproof sealant. S4. Apply thermal insulation coating evenly to the surface of the asbestos-free calcium silicate board in two layers. The thickness of the first layer should be controlled at 10-20mm. After it is completely dry, apply the second layer. The total thickness should reach 40-50mm to form a thermal insulation coating on the surface of the asbestos-free calcium silicate board. S5. Lay wire mesh on the surface of the thermal insulation coating. The overlap width between the wire mesh sheets is 50-60mm. The overlap is tied firmly with binding wire. Then, use high-temperature resistant expansion bolts to fix the wire mesh to the wall. The bolt spacing is 300×300mm to obtain the sealing wall of the coke oven regenerator.

7. The coke oven regenerator sealing wall reinforced with aluminosilicate fiber according to claim 6, characterized in that, In step S4, the preparation method of the high-temperature resistant thermal insulation coating is as follows: sodium hexametaphosphate and deionized water are added to a mixer and stirred for 10-15 minutes. Then, silica powder and silicon nitride powder are added and stirred for another 20-30 minutes. The mixture is then passed through a 300-mesh sieve, hollow ceramic microspheres are added, and the mixture is stirred for 10-15 minutes. Finally, the mixture is transferred to a sand mill and ground for 30-40 minutes to obtain the high-temperature resistant thermal insulation coating.

8. The coke oven regenerator sealing wall reinforced with aluminosilicate fiber according to claim 7, characterized in that, The ratio of sodium hexametaphosphate, deionized water, silica powder, silicon nitride powder and hollow ceramic microspheres is 0.4g:22-25mL:20g:1.8g:38-45g.